Pengaruh Lingkungan Kerja, Beban Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Paparti Pertama di Bekasi - Riska Yuliana; Eri Bukhari; M. Fadhli Nursal (Universitas Kristen Indonesia Toraja, 2024)
The purpose of this research is to determine whether there is an influence of the work environment, workload and work motivation on employee performance at PT. Paparti Pertama. The population in this research were employees of PT. Paparti Pertama, with a total sample 70 respondents. The sampling technique uses random sampling technique using the slovin formula. The data collection method uses quantitative research methods with multiple linear regression analyze and hypothesis testing using the t test and f test with a significance level of 5%. Based on the t test, the work environment has a significant effect on employee performance, workload has a significant effect on employee performance, and work motivation has a significant effect on employee performance. Then based on the f test, the work environment, workload, and work motivation influence employee performance.